Peranan Saluran Distribusi terhadap Penjualan Gula Aren di Kabupaten Lebak - Zakiyya Tunnufus; Iwan Ridwan; Suherman . (E-Journal Studia Manajemen, 2012)
This study aimed to obtain information relating distribution channels on sale of palm sugar at Cibuluh subdistrict Cigemblong Mugijaya, Lebak-Banten. The method used is quantitative method with the type of survey research. The study design is based report distribution channels and sales of micro-unit for four months in May and August 2012. The results showed that distribution channels effect on sales of palm sugar.